2016
DOI: 10.4103/0973-1482.154081
|View full text |Cite
|
Sign up to set email alerts
|

Insights into significant pathways and gene interaction networks in peripheral blood mononuclear cells for early diagnosis of hepatocellular carcinoma

Abstract: Using identified DEGs, significantly changed biological processes such as nucleic acid metabolic process and KEGG pathways such as cytokine-cytokine receptor interaction in PBMCs of HCC patients were identified. In addition, several important hub genes, for example, CUL4A, and interleukin (IL) 8 were also uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In our current study, we found HER2 gene amplification was related to bowel wall invasion and advanced tumor stage, but several other studies have failed to show such relationship. Li et al (2011b) reported an association between HER2 expression and tumor size and distant metastases, and a recent meta-analysis showed HER2 amplification was associated with lymph node metastasis and advanced tumors stage (Sun et al, 2016). The number of studies suggests that HER2 may play some role in tumor progression and would be a valuable prognostic factor for CRC patients (Laurentpuig et al, 2016;Stahler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, we found HER2 gene amplification was related to bowel wall invasion and advanced tumor stage, but several other studies have failed to show such relationship. Li et al (2011b) reported an association between HER2 expression and tumor size and distant metastases, and a recent meta-analysis showed HER2 amplification was associated with lymph node metastasis and advanced tumors stage (Sun et al, 2016). The number of studies suggests that HER2 may play some role in tumor progression and would be a valuable prognostic factor for CRC patients (Laurentpuig et al, 2016;Stahler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Due to a large number of lymphoma subtypes, some genes may show consistent differential expression in multiple lymphoma subtypes that may interfere with the diagnostic specificity. Furthermore, complex gene-gene interactions also affect the accuracy of tumor diagnosis [ 21 ] and prognostic status [ 22 ]. Therefore, a diagnostic model with excellent performance should also be robust and hardly affected by gene-gene interactions.…”
Section: Introductionmentioning
confidence: 99%
“…9 Also, there are experiments utilizing the gene expression on peripheral white blood cells to detect these cancer's in uences. [10][11][12][13][14] Therefore, an invention of markers that are inexpensive, simple, less-invasive and highly accurate can be expected. We focused on the usability of peripheral white blood cells (WBCs), especially peripheral blood mononuclear cells (PBMCs) as a biomarker for liver cancers.…”
Section: Introductionmentioning
confidence: 99%